Intravenous thrombolysis in patients with recent intake of direct oral anticoagulants: a target trial analysis and comparison with reversal agent use - Meinel, Thomas Raphael; Bücke, Philipp; D’Anna, Lucio; Merlino, Giovanni; Aguiar de Sousa, Diana; Poli, Sven; Purrucker, Jan; Strambo, Davide; Romoli, Michele; De Marchis, Gian Marco; Pfeilschifter, Waltraud; Zedde, Marialuisa; et al. (Stroke, 2025)
BACKGROUND: - Intravenous thrombolysis (IVT) in patients with recent ingestion of direct oral anticoagulants (DOACs) is a frequent challenge and remains controversial. The benefit of DOAC reversal before IVT is uncertain. - METHODS: - Using target trial methodology, we analyzed data from 28 comprehensive stroke centers. Patients on DOACs were included if they met IVT criteria, had a National Institutes of Health Stroke Scale score of ≥2, and last DOAC intake within 48 hours or was undeterminable. Safety and efficacy outcomes (symptomatic intracerebral hemorrhage, any intracerebral hemorrhage, major bleeding, 90-day mortality, and good functional outcome [modified Rankin Scale score of 0-2 or return to baseline]) were compared between those receiving IVT versus no IVT and IVT with versus without reversal. In addition, a comparison was made with patients from the New Zealand stroke registry, all of whom underwent reversal with idarucizumab. We adjusted for covariates known to be associated with safety and efficacy outcomes, including age, stroke severity, intended thrombectomy, blood glucose, blood pressure, DOAC reversal, and time from last intake. - RESULTS: - Overall, 1342 patients fulfilled the target trial criteria. The median age was 80 (interquartile range, 73-86) years, median National Institutes of Health Stroke Scale score was 11, 50% were female, and 52% of patients received endovascular therapy. IVT was given in 342 of 1342 (25%) patients. Of these, 141 (41.2%) had verified DOAC intake <12 hours before admission, and 92 (26.9%) within 12 to 24 hours. Symptomatic intracerebral hemorrhage occurred in 10 of 328 (3.0%) of patients receiving IVT and 54 of 921 (5.9%) patients not receiving IVT (adjusted difference, −2.1% [95% CI, −5.3% to +1.2]). Patients receiving IVT were more likely to have good functional outcomes (adjusted difference, +14.4% [95% CI, +7.1% to +21.8%]). Comparing 289 patients with reversal (from the additional New Zealand registry) and 283 patients without reversal before IVT (from the target trial population), there was no significant difference in symptomatic intracerebral hemorrhage, major bleeding, or efficacy outcomes. - CONCLUSIONS: - This target trial confirms previous observational data regarding the safety of off-label IVT in patients with recent DOAC intake. More data and dedicated trials are needed for patients with confirmed high DOAC plasma levels and regarding the efficacy and safety of DOAC reversal before IVT.